Experiences of Older People and Social Inclusion in Relation to Smart “Age-Friendly” Cities: A Case Study of Chongqing, China - Li, Manlin; Woolrych, Ryan (Frontiers in Public Health, 2021)
Whilst cities can be sites of creativity, innovation, and change, they can also reproduce the conditions for the exclusion of vulnerable groups. Older people report experiencing specific barriers to accessing the city and are often excluded from the resources for ageing well. The smart city agenda has attempted to bring about technological change whilst also delivering improved quality of life for urban citizens. Smart technologies are a key element of the smart city and are viewed as having the potential to support the independence, autonomy, and well-being of older people. Yet, there has been little research exploring the role of the smart city in supporting the social inclusion of older people, nor any attempt to link this with key policy drivers on ageing e.g., age-friendly cities and communities. In response, the aim of this paper is to explore the experiences of older people living in a smart city in China and discuss how the smart city and age-friendly agenda can be brought together to support positive social outcomes for older people. The paper presents qualitative findings from a multi-methods approach, including semi-structured interviews, walking interviews and focus groups. A total of 64 older people participated in the research across three diverse neighbourhoods in the case study smart city of Chongqing, China. The findings identified opportunities in the development and deployment of smart city, including the potential for improved health and well-being and social connectedness. Yet in delivering on these benefits, a number of challenges were identified which may widen social inequalities, including inequities in access, issues of safety and security, and exclusion from the co-production of smart city policy and practise. The paper discusses the implications of the findings for future smart city policy and practise, specifically in delivering interventions that support older adults' social inclusion and the delivery of age-friendly cities and communities.